The Learning Model of Islamic Education in Al-Ihsan Integrated Islamic Basic Schools (SDIT) Pasuruan - Yumnah, Siti (Journal of Islamic Education, 2021)
Learning with the Integrated Islamic School system is the integration of the national education system with the principles of Islamic education to educate intelligence, skills, character development and inclusion of moral values ​​of students, so that students have more complete and distinctive personalities. SDIT Al-Ihsan Kota Pasuruan sees to instill a generation of Rabbani who love the Al-Qur'an and instill the example of Rasullullah. In addition, SDIT Al-Ihsan Pasuruan City also plays a role in implementing the 2013 Curriculum, which is based on Islamic characters. This process must go through various learning activities and these various patterns need to be developed by providing material that includes various learning models are under the subject understood, therefore the authors conducted research on various learning models applied in SDIT Al-Ihsan Pasuruan City to find and understand the various character development processes to improve the quality of students with good personalities.